Familial hypocalciuric hypercalcemia in an index male: grey zones of the differential diagnosis from primary hyperparathyroidism in a 13-year clinical follow up - Zajíčková, K; Dvořáková, M; Moravcová, J; Včelák, J; Goltzman, D (Physiological research, 2020)
Familial hypocalciuric hypercalcemia (FHH) type 1, caused by a heterozygous inactivating mutation of the gene encoding the calcium-sensing receptor (CaSR), is characterized by mild to moderate hypercalcemia, hypocalciuria and inappropriately normal or elevated parathyroid hormone (PTH). FHH must be differentiated from primary hyperparathyroidism (PHPT) because parathyroidectomy is ineffective in the former. Herein, we report a 39-year-old male patient with a 13-year history of asymptomatic PTH-dependent hypercalcemia (mean calcium of 2.88 mmol/l; reference range 2.15-2.55 mmol/l) and calcium-to-creatinine clearance ratio (Ca/Cr) ranging from 0.007 to 0.0198, which is consistent with either FHH or PHPT. Although a family history of hypercalcemia was negative, and PET-CT with fluorocholine was suggestive of a parathyroid adenoma, genetic analysis of the CaSR gene identified a heterozygous inactivating mutation NM_000388.4:c.1670G>A p. (Gly557Glu) in exon 6 and a polymorphism NM_000388.4:c.1192G>A p. (Asp398Asn) in exon 4. The G557E mutation has been previously reported in a Japanese family in which all family members with the mutation had Ca/Cr below 0.01 consistent with FHH. The biochemical profile of FHH and PHPT may overlap. Our FHH patient with a G557E CaSR mutation illustrates that the differential diagnosis can be difficult in an index case with no family history, (false) positive parathyroid imaging and higher calciuria than expected for FHH. Calcium intake, vitamin D status and bone resorption might have contributed to the Ca/Cr variations over a 13-year clinical follow up. This case thus emphasizes the irreplaceable role of genetic testing of the CaSR gene when clinical evaluation is inconclusive.
Keywords: dospělí; diferenciální diagnóza; Hypercalcemia; Positron Emission Tomography Computed Tomography; Adult; Hyperparathyroidism, Primary; lidé; PET/CT; vitamin D; hyperkalcemie; následné studie; vápník; Diagnosis, Differential; prognóza; Vitamin D; Follow-Up Studies; Calcium; Male; Receptors, Calcium-Sensing; primární hyperparatyreóza; Prognosis; mužské pohlaví; receptory "calcium-sensing"; Humans